The development and validation of a multidimensional organisational trust measure - Fischer, Sarah; Walker, Arlene; Hyder, Shannon (Frontiers in Psychology, 2023)
Motivation for the study: Workplaces are changing with employees increasingly working remotely and flexibility, which has created larger physical distance between team members. This shift has consequences for trust research and implications for how trust is built and maintained between employees and leaders.Research design: Three studies collectively aimed to demonstrate how employee trust in leaders has adapted to a hybrid work environment. A validation of a seminal multidimensional employee trust in leaders measure was conducted. Also, an alternative multidimensional measure was developed, piloted, and then validated using exploratory and confirmatory factor analyses.Main findings: Findings showed the Affective and Cognitive Trust scale not to be sufficiently reliable or valid after testing with a sample working in a hybrid model of virtual and face to face work environments. However, the new measure demonstrated good reliability and validity.Implication: Findings reinforced that there are behavioural and relational elements to organisational trust, and there are two discreet dimensions to trustworthy behaviour: communication and authenticity.